Evaluation of tyre to road friction estimators, test methods and metrics. (29th November 2010) - Bruzelius, F.; Svendenius, J.; Yngve, S.; Olsson, G.; Casselgren, J.; Andersson, M.; Ronnberg, J.; Lofving, S.
The tyre to road contact friction is one of the most important properties when it comes to manoeuvrability of ground vehicles and information, to driver and vehicle, is of vital importance in critical situations. Different characteristics of different friction estimation methods make it hard to determine and compare performance of estimators. This article is an attempt to define and evaluate the performance of tyre to road friction estimators. The objective of the performance evaluation is to define and grade the performance of estimators based on all sorts of approaches and combinations of these. The result may be used in the context of benchmarking as well as a tool in the development process of the estimator. The test methods and metrics presented are illustrated with a comparative study of three different estimation approaches.